Hormonal change and cytokine mRNA expression in peripheral blood mononuclear cells during the development of canine autoimmune thyroiditis - Choi, E-W (Blackwell Science Inc, 2006)
To elucidate the hormonal change and alteration in cytokine expression in peripheral blood mononuclear cells (PBMC) during the early stage of autoimmune thyroiditis, we have developed a canine model of this disease, in which normal dogs were immunized with bovine thyroglobulin (Tg) and/or canine thyroid extract. Serum samples were collected weekly, anti-canine Tg antibody was measured by enzyme-linked immunosorbent assay (ELISA) and thyroid stimulating hormone (TSH) and total T4 levels by radioimmunoassay. We also assayed T lymphocyte proliferation in response to Tg, as well as measuring cytokine mRNA by semiquantitative reverse transcription–polymerase chain reaction (RT–PCR). All six dogs immunized with bovine Tg had both canine Tg autoantibody and anti-T4 antibody. When the sample from the highest TgAA titre time-point was compared with baseline the expression of mRNA encoding the Th1-type cytokine such as interferon (IFN)-γ, interleukin (IL)-18 and IL-15 was increased during the development of autoimmune thyroiditis. Expression of the Th2-type cytokine, IL-6 showed minimal change and IL-4 expression was not detected in any of the samples. Expression of the T suppressive cytokine, IL-10 and transforming growth factor (TGF)-β was increased in the presence of antigen stimulation. These findings suggest that, although autoimmune thyroiditis is an organ-specific autoimmune disease, systemic cytokine mRNA expression is also changed.